Biocomposites based on poly(butylene succinate) and curaua: Mechanical and morphological properties. (August 2015) - Frollini, Elisabete; Bartolucci, Nadia; Sisti, Laura; Celli, Annamaria
Abstract: Biocomposites based on poly(butylene succinate) (PBS) and curaua fibers have been produced by compression molding, and investigated as a function of fiber length and amount. Mechanical tests, water uptake and morphology studies were carried out in order to assess the composite features according to the characteristics of the reinforcing agents. It turns out that the impact and flexural strengths increase with fiber content. Moreover, the fiber length, varying from 1 to 4 cm for the composite reinforced with 20 wt% of fiber, influences impact strength, which is higher for shorter than for longer fibers. However, flexural strength is not greatly influenced by the length of the fibers. Water uptake studies reveal a higher sensitivity of the material to fiber content rather than fiber size. Biocomposites, which are characterized by enhanced mechanical properties as compared to PBS, can have different applications, for example in rigid packaging or interior car parts.